The Application of IoT-based Water Pressure Monitoring System - Chew, Kim Mey; Yiiong, Siew Ping; Nancy, Bundan; Syvester Tan, Chiang Wei (2021)
The study was stimulated by local utilities to improve their reputation in the era of water supply in residential areas, particularly the issue of low water pressure. The current low water pressure situation is highly dependent on complaints from residents in the supply area. This resulted in an extended period of time to solve the problem. Therefore, an IoT-based water pressure measuremeter was proposed. The proposed measurement device was used to detect low water pressure at the residential area or internal area that is away from the water main. The proposed solution is developed based on the principle of IoT architecture which covers the perception layer, network layer and application layer. The perception layer is composed of Arduino as microcontroller, GSM and WiFi shield as communication and water pressure sensor as transducer. WiFi and GSM shield provide communication services within the network layer. For the application layer, an IoT platform was chosen for data analysis and visualisation. The water pressure variation taken at two different places in urban areas. Two datasets were collected at Location 1 and four datasets were collected at Location 2. Each dataset has a 24-hour time frame. Preliminary findings were obtained and presented in this paper. The results showed the water pressure pattern within 24 hours. The study shows that real-time monitoring of water pressure contributes to a better standard of living for residents, as well as helping authorities find efficiencies and increase profits.